Multivariate Analysis of Factors Associated with Hemoglobin Levels among CKD Patients undergoing Hemodialysis - Fauzan, Suhaimi; Martadi, Kharisma Aji; Fradianto, Ikbal; Maulana, Muhammad Ali; Herman, Herman (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Chronic Kidney Disease (CKD) is one of the silent killer diseases that often experience an increase in incidence every year. Common problem that often arises in someone with CKD is a decrease in hemoglobin levels. This study aims to identify and analyze factors related to hemoglobin levels among CKD patients undergoing hemodialysis. This was a correlational study with cross sectional approach. The study was conducted on March 21 – 31, 2022. The study population consisted of 90 CKD patients undergoing hemodialysis at Doctor Soedarso Regional General Hospital (as of January 2022). The samples involved 73 people who were selected using purposive sampling technique. The independent variables included age, gender, ethnicity, education, employment status, smoking history, creatinine and urea levels, while the dependent variable in this study was hemoglobin levels. Bivariate analysis in this study applied chi-square, Kendall’s, and independent sample t tests, while the multivariate test applied logistic regression. The analysis results obtained p values for age, employment status, smoking history, creatinine levels, and urea levels of 0.069 (OR=8.4), 0.418 (OR=2.4), 0.286 (OR=4.3), 0.000, and 0.323, respectively. It can be concluded that there was an effect of creatinine levels on changes in hemoglobin levels among CKD patients undergoing hemodialysis. Patients undergoing hemodialysis are recommended to control the amount and source of protein intake, adjust physical activity according to age and ability, and pay attention to the regular dialysis schedule